2023
DOI: 10.1111/cod.14306
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic contact urticaria to milk in an adult patient with severe atopic dermatitis

Abstract: Dog cosmetics can directly cause allergic contact dermatitis (ACD)in owners, groomers or veterinarians, and/or consort ACD from touching dogs, including in those aware of pre-existing sensitisations. 1 A detailed clinical history is essential to identify such exposure. METHODSIn January 2022, a survey was conducted of all 163 dog cosmetic products sold face-to-face in five high street pet stores in Southampton, UK. The quality of labelling and the number of common allergens present were recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In this contrast, the combination could also be used as additional curative agents to restore and sustain dental health [ 77 ]. Allergic reactions have also been reported to chamomile, which was followed by skin allergy after topical appliance and bronchial constriction through systemic administration [ 78 , 79 ]. In a study, Aggarwal and Chaudhary suggested that the mouth rinse of Matricaria chamomilla L. is effective for clinical and microbiological illustration for chronic periodontitis.…”
Section: Medicinal Plants Used To Treat Gingivitis and Periodontitismentioning
confidence: 99%
“…In this contrast, the combination could also be used as additional curative agents to restore and sustain dental health [ 77 ]. Allergic reactions have also been reported to chamomile, which was followed by skin allergy after topical appliance and bronchial constriction through systemic administration [ 78 , 79 ]. In a study, Aggarwal and Chaudhary suggested that the mouth rinse of Matricaria chamomilla L. is effective for clinical and microbiological illustration for chronic periodontitis.…”
Section: Medicinal Plants Used To Treat Gingivitis and Periodontitismentioning
confidence: 99%